Experimental investigation of cavitation using refrigerant in a two-phase flow system - Alrifaai, Hatim Hamid (Kansas State University, 2018)
Cavitation is a phase change process and its conversion of fluid from liquid to vapor requires pressure reduction. In this thesis, cavitation of R134a refrigerant is evaluated experimentally. This work is part of an ongoing project that seeks to develop a novel cooling cycle based on the cooling potential of the fluid during cavitation. A blowdown system was designed, built, and used for conducting the experiments. This system included a special test section containing a unique converging-diverging nozzle system designed for this investigation. In the end, cavitation was achieved by flowing the test fluid through a converging-diverging nozzle. As the fluid flows through the nozzle throat, the velocity increases while the pressure decreases and cavitation occurs when its static pressure drops below its vapor pressure. The onset of cavitation was evaluated by measuring pressure, temperature, and refrigerant flow rate, and by visualizing the flow using a high-speed video camera.
Keywords: Cavitation